The Impact of Decentralization on Forest Governance in Southeast Asia - Alves, Livia; Mendes, Clara; Rocha, Thiago (Yayasan Adra Karima Hubbi, 2024)
Decentralization has emerged as a significant trend in forest governance across Southeast Asia, aiming to enhance local participation and improve resource management. While intended to empower local communities, the actual impacts of decentralization on forest governance remain poorly understood. This study investigates how decentralization affects governance structures, stakeholder engagement, and environmental outcomes in the region. The research aims to assess the effects of decentralization on forest governance by examining case studies from selected Southeast Asian countries. The study seeks to identify both positive and negative outcomes, focusing on how local governance influences forest conservation and management practices. A mixed-methods approach was utilized, combining qualitative interviews, surveys, and document analysis. Data were collected from government officials, local community members, and NGOs involved in forest management. Comparative analysis of case studies from Indonesia, Malaysia, and the Philippines provided insights into the varying impacts of decentralization. Findings indicate that decentralization can enhance local participation and accountability in forest governance. However, challenges such as inadequate capacity, corruption, and conflicting interests often hinder effective implementation. Case studies revealed diverse outcomes, where successful decentralization led to improved resource management, while in other instances, it exacerbated existing inequalities. The research highlights the complex relationship between decentralization and forest governance in Southeast Asia. Effective decentralization requires supportive policies, capacity building, and genuine stakeholder engagement to achieve sustainable forest management. The study underscores the need for ongoing evaluation of decentralization processes to ensure they meet both conservation and community objectives effectively.